Genetic variants involved in the cGAS-STING pathway predict outcome in patients with metastatic colorectal cancer: Data from FIRE-3 and TRIBE trials. (September 2022) - Wang, Jingyuan; Xiao, Yi; Loupakis, Fotios; Stintzing, Sebastian; Yang, Yan; Arai, Hiroyuki; Battaglin, Francesca; Kawanishi, Natsuko; Jayachandran, Priya; Soni, Shivani; Zhang, Wu; Mancao, Christoph; et al.
Abstract: Background: The activation of stimulator of interferon genes (STING) was reported to enhance cetuximab-mediated natural killer cell activation and dendritic cell maturation. Polymorphisms in genes in the cyclic GMP-AMP synthase (cGAS)-STING pathway may affect innate immune response. Therefore, we hypothesised that genetic variants in the cGAS-STING pathway may predict the efficacy of cetuximab-based treatment in patients with metastatic colorectal cancer. Methods: Genomic DNA from blood samples of patients enrolled in FIRE-3 (cetuximab arm, n = 129; bevacizumab arm, n = 107) and TRIBE (bevacizumab arm, n = 215) was genotyped using the OncoArray-500K bead chip panel. Seven selected single nucleotide polymorphisms in 3 genes (cGAS, STING and interferon B1 (IFNB1)) were analysed for the association with overall survival and progression-free survival. Results: In the cetuximab cohort, patients with STING rs1131769 any T allele showed significantly shorter overall survival (36.3 versus 56.1 months) than carriers of C/C in both univariate [hazard ratio (HR) = 2.08; 95% confidence interval (CI): 1.06–4.07; P = 0.03] and multivariate (HR = 2.98; 95% CI: 1.35–6.6; P = 0.0085) analyses; patients carrying IFNB1 rs1051922 G/A and A/A genotype showed a significantly shorter progression-free survival than carriers of G/G allele in both univariate (G/A versus G/G, 10.2 versus 14.1 months, HR = 1.84; 95% CI 1.23–2.76; A/A versus G/G, 10.7 versus 14.1 months, HR = 2.19; 95% CI 0.97–4.96; P = 0.0077) and multivariate analyses (G/A versus G/G, HR = 2; 95% CI 1.22–3.3; A/A versus G/G, HR = 2.19, 95% CI 0.92–5.26, P = 0.02). These associations were not observed in the bevacizumab arm of FIRE-3 or TRIBE. Conclusion: These results suggest for the first time that germline polymorphisms in STING and IFNB1 genes may predict the outcomes of cetuximab-based treatment in patients with metastatic colorectal cancer. Highlights: Predictive values of SNPs involved in cGAS-STING pathway were tested. STING rs1131769 was significantly associated with OS in patients receiving cetuximab-based first-line treatment.IFNB1 rs1051922 was significantly associated with PFS in patients receiving cetuximab-based first-line treatment. Associations between tested SNPs and bevacizumab efficacy were not significant.